R&D IN FUNCTION OF DIRECT PUBLIC SUPPORTS TO SMEs: AN EXPLORATORY STUDY IN TURKEY - Filiz Giray; Mehmet Çına; Simla Güzel (Economic Review)
The globalization has increased the importance of research and development (R&D) activity and of technological advancements, especially in information and communication technologies. This case is valid for small and medium sized enterprises (SMEs) which have taken a crucial place in all economies. Since R&D activities have high costs and public features, these activities cannot be carried out by firm, especially SMEs’ fiscal sources. Direct supports play a key-role in most countries. In related literature, many researchers have stressed that direct public supports towards R&D activities are important for SMEs. Recently, the requirement of public support in R&D activities has been increased in Turkey, just as in most countries. The study investigated both the relationship between direct public supports and R&D in SMEs and the factors determining the using level of R&D supports with an empirical study for Turkey as a sample. A survey of 600 SMEs in Turkey was conducted by a research company on behalf of the authors. The survey data have been estimated by logistic regression analysis and allow us to indicate the factors which determine the using level of direct public supports of SMEs. According to the logistic regression model, the determiner factors are the information level of firms on R&D supports, available convenient support kind, the number of licenses and patents, supply of new product to market etc., in order to increase the possibility for benefit from supports. The most important factor is the fact that SMEs obtain licenses and patents. These results provide contribution to improving R&D activities in SMEs.